Long-term benefits from temporary migration: Does the gender of the migrant matter? - Sanjaya DeSilva (Levy Economics Institute of Bard College, 2013)
Utilizing a nationally representative sample of households from Sri Lanka, this study examines gender differences in the long-term impact of temporary labor migration. We use a propensity score matching (PSM) framework to compare households with return migrants, households with current migrants, and equivalent nonmigrant households in terms of a variety of outcomes. Our results show that households that send women abroad are relatively poor and utilize migration to catch up with the average household, whereas sending a man abroad allows an already advantaged household to further strengthen their economic position. We also find that remittances from females emphasize investment in home improvements and acquisition of farm land and nonfarm assets, whereas remittances of men are channeled more toward housing assets and business ventures.
Keywords: F22; F24; J61; O15; 330; migration; remittances; gender; Sri Lanka